2018
DOI: 10.1007/s12035-018-0948-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel Defense by Metallothionein Induction Against Cognitive Decline: From Amyloid β1–42-Induced Excess Zn2+ to Functional Zn2+ Deficiency

Abstract: The role of metallothioneins (MTs) in cognitive decline associated with intracellular Zn dysregulation remains unclear. Here, we report that hippocampal MT induction defends cognitive decline, which was induced by amyloid β (Aβ)-mediated excess Zn and functional Zn deficiency. Excess increase in intracellular Zn, which was induced by local injection of Aβ into the dentate granule cell layer, attenuated in vivo perforant pathway LTP, while the attenuation was rescued by preinjection of MT inducers into the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…In the hippocampus, Aβ 1–42 released into the extracellular compartment can capture Zn 2+ , which is estimated to be approximately 10 nM in the extracellular fluid 13 , even at 500 pM Aβ 1–42 in vivo . We have reported that Aβ 1–42 takes Zn 2+ as a cargo into dentate granule cells in the normal brain, followed by cognitive decline 1416 . Although the mechanism of Zn-Aβ 1–42 uptake remains to be solved, extracellular Zn 2+ is essential for Aβ 1–42 uptake into dentate granule cells 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In the hippocampus, Aβ 1–42 released into the extracellular compartment can capture Zn 2+ , which is estimated to be approximately 10 nM in the extracellular fluid 13 , even at 500 pM Aβ 1–42 in vivo . We have reported that Aβ 1–42 takes Zn 2+ as a cargo into dentate granule cells in the normal brain, followed by cognitive decline 1416 . Although the mechanism of Zn-Aβ 1–42 uptake remains to be solved, extracellular Zn 2+ is essential for Aβ 1–42 uptake into dentate granule cells 15 .…”
Section: Introductionmentioning
confidence: 99%
“…44,45) The vulnerability seems to be linked with age-related modification of extracellular Zn 2+ influx, which is induced by glutamate and Aβ 1-42 in the extracellular compartment. 33,41,46,47)…”
Section: Modification Of Intracellular Zn 2+ Buffering With Agingmentioning
confidence: 99%
“…59) The aggregating property of Aβ 1-42 is rapidly promoted with Zn 2+ , resulting in much higher affinity of Aβ 1-42 to Zn 2+ than that of Aβ 1-40 , and the K d values of Zn 2+ to Aβ 1-42 are in the range of 3-30 nM. 46) Aβ 1-42 , unlike Aβ 1-40 , captures extracellular Zn 2+ at high picomolar levels, and the formation of Zn-Aβ 1-42 in the extracellular compartment is essential for Aβ 1-42 uptake into dentate granule cells, followed by cognitive decline (Fig. 2).…”
Section: Impact Of Modified Intracellular Zn 2+ Buffering On Neurodegmentioning
confidence: 99%
See 2 more Smart Citations